Modified Tubularised Incised Plate Urethroplasty (TIPU) with Dorsal Inlay Preputial Skin Graft: An Outcome Evaluation of 21 cases (Bangladesh Medical Journal, 2019)
There are different techniques of hypospadias repair, out of them TIPU is widely practiced and popular procedure. Here a midline incision is made over the urethral plate for widening of urethral lumen and creation of neomeatus. Meatal stenosis may subsequently develop at new meatus and it is the limitation of this procedure.  In this study TIPU procedure is modified by applying preputial skin graft on incised urethral plate in dorsal inlay fashion and outcome is evaluated. In this prospective study total 21 patients with distal penile hypospadias underwent repair between 2016 and 2017. TIPU urethroplasty was done as usual along with application of a preputial skin graft on midline incised urethral plate. Tubularization was done over appropriate sized catheter and double layers bilateral Dartos flap was applied to cover the suture line. SPC catheterization was done in every patient. On 14th post-operative day urethral catheter was removed and on the same day if patient voids satisfactorily, SPC catheter was also removed. The outcome was evaluated according to the Hypospadias Objective Scoring Evaluation (HOSE) system. 95.23% of the patients achieved apical neomeatus and 90.47% of slit like meatal shape. Mild degree chordee and normal caliber urinary flow was in 9.5% and 95.23% of the patients respectively. 4.76% of the patients developed urethrocutaneous fistula. Dorsal inlay preputial skin grafting is a very simple and feasible technique to maximize the outcome of TIPU procedure. However, multicenter and high volume data are needed for its wide application.Bangladesh Med J. 2018 Jan; 47 (3): 9-12